ANALISIS RELEVANSI DAN EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK DALAM PEMBELAJARAN PAI: KAJIAN SYSTEMATIC LITERATURE REVIEW - Darul Mustofa; Ratu Vina Rahmatika; Ayub Kumalla; Akbar Rahman; Ahmad Saeful Ahyar (STKIP Pesisir Selatan, 2026)
This learning model emphasizes that the learning process has a focal point on cooperation between students in small groups, where each individual has responsibility for a certain part of the material that has been divided by the educator and then teaches it to the other group members. This study aims to analyze the relevance and effectiveness of the Jigsaw-type cooperative learning model on students learning outcomes and learning activities in Islamic Religious Education (PAI). The method used is a Systematic Literature Review (SLR) based on PRISMA guidelines, covering scientific articles from the 2021-2024period obtained through Google Scholar, DOAJ, and SINTA-indexed journals, using the stages of identification, screening, eligibility, and inclusion. The results of the study indicate that the Jigsaw model is relevant in PAI learning and effective in improving learning outcomes, particularly in conceptual understanding and material retention. In addition, this model also enhances students learning activities in terms of participation, interaction, and collaboration during the learning process. These findings suggest that the Jigsaw model supports more active, collaborative, and meaningful learning.